2013
DOI: 10.1088/0004-6256/145/4/107
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium, Barium, Lanthanum, and Europium Abundances in Open Clusters

Abstract: We present an analysis of the s-process elements Zr, Ba, and La and the r-process element Eu in a sample of 50 stars in 19 open clusters. Stellar abundances of each element are based on measures of a minimum of two lines per species via both equivalent width and spectrum synthesis techniques. We investigate cluster mean neutron capture abundance trends as a function of cluster age and location in the Milky Way disk and compare them to results found in other studies in the literature. We find a statistically si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 54 publications
8
99
3
Order By: Relevance
“…While a number of OCs are consistent with the average of the stars in the disk, a significant fraction show a [La/Fe] about 0.2-0.3 dex larger than in the Sun. These departures are beyond the present error estimations, but they could be explained within the present systematic uncertanties highlighted comparing the results from different authors (e.g., Yong et al 2012;Jacobson & Friel 2013, and references therein).…”
Section: Etc) More In Generalcontrasting
confidence: 48%
See 2 more Smart Citations
“…While a number of OCs are consistent with the average of the stars in the disk, a significant fraction show a [La/Fe] about 0.2-0.3 dex larger than in the Sun. These departures are beyond the present error estimations, but they could be explained within the present systematic uncertanties highlighted comparing the results from different authors (e.g., Yong et al 2012;Jacobson & Friel 2013, and references therein).…”
Section: Etc) More In Generalcontrasting
confidence: 48%
“…The ages were calculated consistently, according to Carraro & Chiosi (1994). In the figures we include abundances obtained earlier (Mishenina et al 2013b(Mishenina et al , 2014 with measurements from other authors, for a number of OCs (D' Orazi et al 2009;Pancino et al 2010;Carrera & Pancino 2011;Maiorca et al 2011;D' Orazi et al 2012;Reddy et al 2012Reddy et al , 2013Bragaglia et al 2008;Yong et al 2005;Jacobson & Friel 2013) and the data for the thin disk stars were taken from the study by Mishenina et al (2013a).…”
Section: Etc) More In Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model does not take into account the mass transfer that occurs when the planet fills its Roche lobe. This phase has been modelled by, for example Valsecchi et al (2014Valsecchi et al ( , 2015 and Jackson et al (2016), who found that its duration depends in a critical way on the interplay between the planet mass loss, which tends to increase the semi-major axis, and the stellar tides, which shrink it. We also note the above-mentioned publications concerning evaporation issues.…”
Section: A Possible Engulfment Scenario Of a Planetary Companionmentioning
confidence: 99%
“…In recent years, the abundances of the s-process elements in open clusters have become a target of intense study (e.g., D 'Orazi et al 2009'Orazi et al , 2012Jacobson et al 2011;Maiorca et al 2011;Jacobson & Friel 2013;Mishenina et al 2013Mishenina et al , 2015. This (2011) have proposed a scenario with models of extra-mixing phenomena with high efficiency in the production of the neutron source 13 C in stars with Nordhaus et al 2008;Nucci & Busso 2014;Trippella et al 2014).…”
Section: Discussionmentioning
confidence: 99%